Effect of surface water-groundwater exchange on heavy metal transport in the vegetated rivers - Linlin Li; Jiahao Zou; Hang Li; Jiadong He; Hao Zhang; Canyong Li (Journal of Contaminant Hydrology, 2026)

Integrated computational and in vivo evidence prioritizes MYH6 as a candidate node in PFOS-associated HCM-like cardiac remodeling - Hao Gao; Li Ma; Shiyi Tan; Xulei Zuo; Wei Wang; Linlin Zhang; Qin Ding; Rongli Sun; Yuepu Pu; Juan Zhang (Environmental Pollution, 2026)

Plasma-based biomimetic antigen outpost synergizes with immune checkpoint blockade to enhance antitumor immunity via dual inhibition of SOCS1 and PD-L1 pathways in dendritic cells - Siyuan Meng; Fangnan Lv; Jieqing Chen; Linlin Tao; Hao Guo; Danhui Wang; Jie Sun; Jian Li; Ning Liu; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2026)

Spatial heterogeneity of ice phenology in large lakes of Xinjiang, China - Kangzheng Zhong; Jiaxin Hao; Puzhe Huo; Chunpeng Chen; Linlin Cui; Liping Xu; Zhijun Li; Jiang Li; Guanghui Wei (Regional Environmental Change, 2026)

Retraction notice to “Study on the effect of SDBS and SDS on deep coal seam water injection” [Sci. Total Environ. 856 (2023) 158930] - Lianman Xu; Yajing Li; Linlin Du; Fengshuo Yang; Runjie Zhang; Hao Wei; Gang Wang; Zhe Hao (Science of The Total Environment, 2026)

Activating Na4 site via crystalline-phase-engineering enables charge redistribution and stress mitigation in Na4Fe3(PO4)2P2O7 cathodes - Linlin Zhou; Danjing Yang; Shuting Wen; Ling Chen; Chenwei Li; Haifeng Yu; Hao Jiang; Chunzhong Li (Science Bulletin, 2026)

Enzymatic synthesis of oligodextran with prebiotic potential by a recombinant dextransucrase from Latilactobacillus sakei L3 - Binbin Wang; Linlin Hao; Kaiyue Zuo; Xiaojing Liu; Huimin Yao; Weizhong Liu; Fangkun Zhao; Lei Pan; Baomei Wu (Carbohydrate Polymers, 2026)

Engineering carbon dots with amplified peroxidase-mimetic activity for dual-modal colorimetric-photothermal sensing of organophosphorus and carbamate pesticides - Na Gao; Yajuan Zhao; Yuhan Huang; Yanke Zhou; Linlin Yang; Liguo Ji; Hao Zhu; Wenjie Ren; Guangjie He (Analytica Chimica Acta, 2026)

Performance and wastewater treatment efficiency of artificially prepared aerobic granular sludge - Xuanzhe Yan; Jinlong Wang; Kailong Liu; Hao Wu; Wei He; Yongmei Zhang; Linlin Tong; Su Li; Zhaoyang You (Biodegradation, 2026)

Progressive Failure Behavior of Fracture-Grouted Sandstone After High-Temperature Treatment During Uniaxial Loading: Insights from AE-DIC Experiments and Grain-Based Cohesive Modeling - Haoyang Zhang; Annan Jiang; Fu Zheng; Linlin Liu; Minghao Hao (Rock Mechanics and Rock Engineering, 2026)

Linking genetic connectivity and ecological niche similarity to inform coastal biosecurity management: a global case study of Mytilopsis sallei - Hao Dong; Linlin Zhao; Liuyi Huang; Xiaoyang Wang; Changdong Liu (Ocean & Coastal Management, 2026)

Carbon dots/konjac glucomannan/starch anti-freezing gel: development and cryoprotective coating for beef preservation - Linlin Zhao; Zeyue Zhao; Wenqin Gu; Huinan Jiang; Hao Xu; Suqing Sun; Xiangren Meng (Food Research International, 2026)

Biochar and manure amendments mitigate chemical-fertilizer-induce negative effects on soil microbiomes, with implications for crop productivity gain - Pan Jiang; Hao Huang; Jinmeng Hu; Linlin Wang; Yuping Zhang; Xiangmin Rong; Jianwei Peng; Gongwen Luo (Applied Soil Ecology, 2026)

Ultrastructural Evidence of Altered Dendritic Morphology in the Prefrontal Cortex of Alzheimer's Model Rats - Jinyue Guo; Jing Liu; Yanchao Zhang; Jiazheng Liu; Hao Zhai; Linlin Li; Hua Han (Neuroscience Bulletin, 2026)

Deubiquitinases in liver diseases: from mechanisms to targeted therapy - Zhenge Zhang; Wanli Duan; Yixiang Wang; Peng Hao; Linlin Chen; Ziyi Hao; Ming He; Yingli Wu; Hao Luo (Science China Life Sciences, 2026)

Machine learning based prediction of mechanical properties in carbon fiber recovered through pyrolysis - Xiang Guo; Tian Li; Chunting Liu; Meng Zhang; Hao Li; Jinrui Li; Yihua Zhang; Chunmei Zeng; Shuwu Wei; Linlin Pei; Fang Liu; Da Chen (Waste Management, 2026)

Interactive effect of children’s copper exposure and socioeconomic status on preschoolers’ cognitive development - Hualong Zhen; Linlin Zhu; Xuemei Hao; Jingru Lu; Yufan Guo; Chunmei Liang; Juan Tong; Fangbiao Tao; Jiong Li; Kun Huang (NeuroToxicology, 2026)

Inhalable tetrahedral DNA nanoplatforms for dual-barrier penetration and sustained deep-lung delivery of small-molecule drugs - Fenglin Jiang; Qi Han; Hao Deng; Jiaqi Li; Alimire Alifu; Zhuo Chen; Linlin Deng; Xiaoxiao Cai; Yu Chen; Yunfeng Lin (Chemical Engineering Journal, 2026)

LARS1 knockdown suppresses the biological activities of thyroid cancer cells by stimulating autophagy - Congwen Jin; Chuanhong Li; Linlin Chen; Hao Liu; Yousheng Yu; Benxin Chen (Tissue and Cell, 2025)

Engineering yeast expression platforms: Advanced strategies for heterologous protein production and glycosylation modification - Hao Li; Taichi Chen; Zikun Zhang; Qiyi Jiang; Weigang Yuwen; Linlin Qu; Rongzhan Fu; Chenhui Zhu; Huan Lei; Daidi Fan (Chemical Engineering Journal, 2025)

Pilot-scale investigation of polyhydroxyalkanoates synthesis using mixed microbial cultures from fermented thermally hydrolyzed sludge - Yun He; Kuixiao Li; Yu Zhang; Gang Wang; Jing Chang; Shan Hao; Linlin Wei; Xu Xing (Bioresource Technology, 2025)

Terpenoids from Aglaia edulis and their lung epithelial cells protective activity - Ling Li; Qianqian Yin; Yanping Zhang; Linlin Yang; Yue Gao; Jinle Hao; Bin Lin; Di Zhou; Ning Li (Phytochemistry, 2025)

Seismic performance of rubberized concrete double-column piers confined by corrugated steel tubes - Linlin Zhang; Baodong Liu; Mingyang Feng; Haibo Sun; Changshun Hao (Engineering Structures, 2025)

Salvianolic Acid B and Ginsenoside Rg1 Combination Attenuates Cerebral Edema Accompanying Glymphatic Modulation - Lingxiao Zhang; Yanan Shao; Zhao Fang; Siqi Chen; Yixuan Wang; Han Sha; Yuhan Zhang; Linlin Wang; Yi Jin; Hao Chen; Baohong Jiang (Neuroscience Bulletin, 2025)

DBENet: dual-branch encoder network based on the visual state space model for semantic segmentation of remote sensing image - Hengyou Wang; Hao Liu; Lianzhi Huo; Linlin Chen; Qiang He (International Journal of Remote Sensing, 2025)

Identifying hundredfold carbon emission gaps in multiple resource recycling routes of construction waste via process and hybrid life cycle assessment - Rui Chen; Haiyuan Wu; Junjie Li; Hao Wang; Lanxin Li; Linlin Sun; Fumin Ren (Waste Management, 2025)

Microseismic criterion for dynamic risk assessment and warning of roadway rockburst induced by coal mine seismicity - Lianpeng Dai; Xin Zhao; Yishan Pan; Hao Luo; Yanan Gao; Aiwen Wang; Linlin Ding; Peng Li (Engineering Geology, 2025)

Advances in preclinical studies of ginsenoside Rh2 in antitumor therapy - Zheng Xu; Guanghuan Shen; Zhihua Xing; Jianghan Luo; Yu Zhu; Xuan Liu; ShiHao Li; Hao Wang; Linlin Cui (Medicinal Chemistry Research, 2025)

Seismic behavior of prefabricated-assembled frames with corrugated steel tube confined connections and piers: Experiments, numerical models, and design - Linlin Zhang; Baodong Liu; Mingyang Feng; Haibo Sun; Changshun Hao (Engineering Structures, 2025)

Hesperidin-loaded self-assembled supramolecular hydrogel based on quaternized chitosan as efficient photothermal antibacterial dressing for MRSA-infected wound healing - Yamin Xiong; Yi Hao; Linlin Ding; Jinjin Li; Yuan Cao; Shuhui Fan; Fangxia Guan; Leiliang He (Carbohydrate Polymers, 2025)

Lacticaseibacillus paracasei SB27 enhances its gastrointestinal tolerance, adhesion and colonization by producing biofilm - Yinxue Liu; Linlin Hao; Yisuo Liu; Lu Jiang; Huaxi Yi (Food Bioscience, 2025)

Nine-year biochar history increases topsoil nitrogen stocks and reduces the refractory organic nitrogen fractions in deep soils - Di Wang; Shuai Liu; Liwei Hao; Qi Yue; Linlin Jiang; Yu Lan; Wenfu Chen (Journal of Soils and Sediments, 2025)

Protective effects of resveratrol on honeybee health: Mitigating pesticide-induced oxidative stress and enhancing detoxification - Linlin Liu; Min Shi; Yanyan Wu; Jiali Hao; Junxiu Guo; Shanshan Li; Pingli Dai; Jing Gao (Pesticide Biochemistry and Physiology, 2025)

Planning conservation priority areas for marine mammals accounting for human impact, climate change and multidimensionality of biodiversity - Linjie Li; Yanli Tang; Hao Dong; Linlin Zhao; Changdong Liu (Journal of Environmental Management, 2025)

Transcranial Magnetic Stimulation Alleviates Spatial Learning and Memory Impairment by Inhibiting the Expression of SARM1 in Rats with Cerebral Ischemia–Reperfusion Injury - Linlin Jiang; Yule Wang; Yingxi He; Ying Wang; Hao Liu; Yu Chen; Jingxi Ma; Ying Yin; Lingchuan Niu (NeuroMolecular Medicine, 2025)

Convert iron tailings waste into a novel Mg-Fe-Al hybrid magnetic coagulant for enhanced pretreatment of swine wastewater - Linlin Hao; Jingshuang Yan; Jiaoying Guo; Nannan Wang; Ming Zeng (Journal of Environmental Chemical Engineering, 2025)

Mechanism Study of Cu(II)/Cd(II)/Ni(II) Ions Adsorption by Montmorillonite-Based Geopolymers: Molecular Dynamics Simulation and Structural Characterization - Dongmei Jia; Ming Zeng; Linlin Hao; Jingguo Cao (Water, Air, & Soil Pollution, 2025)

Physicochemical properties and structure of rice dough and protein based on TGase combined with sodium metabisulfite modification - Xuyang Ren; Wanshan Yang; Huining Zhang; Yang Yu; Xiaofeng Hu; Hongchen Fan; Linlin Liu; Mingshou Lv; Ying Sun; Yanguo Shi; Yanling Hao; Fenglian Chen (Food Chemistry, 2025)

TRIM21 Promotes Endothelial Cell Activation via Accelerating SOCS3 Ubiquitination Degradation in Atherosclerosis - Zhenxuan Hao; Yihuan Wang; Linlin Chen; Yanjun Zhou; Dezhou Fang; Wenxiang Yao; Lili Xiao; Yanzhou Zhang (Cardiovascular Toxicology, 2025)

Bivariate Spatial Autocorrelation Analysis of Keshan Disease and Hair Selenium of Residents in Heilongjiang Province, China - Jiacheng Li; Guijin Li; Cheng Wang; Huixin Sun; Linlin Du; Shuxiu Hao; Qingyu Zeng; Cunqi Lv; Yu Zhang; Xinshu Wang; Zhifeng Xing; Tong Wang (Biological Trace Element Research, 2025)

Spatial Clusters of Low Serum Selenium: the Priorities of Selenium Supplementation to Residents of Keshan Disease Endemic Areas - Qingyu Zeng; Guijin Li; Ruixiang Wang; Cunqi Lv; Shuxiu Hao; Jiacheng Li; Huixin Sun; Linlin Du; Cheng Wang; Yu Zhang; Xinshu Wang; Yuehui Jia; et al. (Biological Trace Element Research, 2025)

Lactic acid bacteria in relieving constipation: mechanism, clinical application, challenge, and opportunity - Tong Zhang; Wenxu Liu; Huimin Lu; Ting Cheng; Linlin Wang; Gang Wang; Hao Zhang; Wei Chen (Critical Reviews in Food Science and Nutrition, 2025)

Corrigendum to “The latest activity of the slope fault zone (Pearl River Mouth) in northern South China Sea and implications for earthquake hazard assessments” [166 (2024) 106937] - Liangwei Lv; Zhigang Li; Dawei Wang; Weitao Wang; Xiangming Dai; Fanchang Zeng; Linlin Li; Hao Liang; Gege Hui; Weiwang Long; Peizhen Zhang (Marine and Petroleum Geology, 2025)

Widespread presence of gut bacterium Glutamicibacter ectropisis sp. nov. confers enhanced resistance to the pesticide bifenthrin in tea pests - Xiayu Li; Ting Fang; Tian Gao; Hao Gui; Ying Chen; Linlin Zhou; Yong Zhang; Yunqiu Yang; Letian Xu; Yanhua Long (Science of The Total Environment, 2024)

Comparative analysis of climate-induced habitat shift of economically significant species with diverse ecological preferences in the Northwest Pacific - Wanchuan Dong; Xinlu Bai; Linlin Zhao; Hao Dong; Changdong Liu (Frontiers in Marine Science, 2024)
The Northwest Pacific Ocean is the most productive fishing ground in the Pacific Ocean, with a continuous rise in water temperature since 1990. We developed stacked species distribution models (SSDMs) to estimate the impacts of climate change on the distribution dynamics of economically significant species under three climate change scenarios for the periods 2040-2060 and 2080-2100. Overall, water temperature is the most important factor in shaping the distribution patterns of species, followed by water depth. The predictive results indicate that all the species show a northward migration in the future, and the migration distance varies greatly among species. Most pelagic species will expand their habitats under climate change, implying their stronger adaptability than benthic species. Tropical fishes are more adaptable to climate change than species in other climate zones. Though limitations existed, our study provided baseline information for designing a climate-adaptive, dynamic fishery management strategy for maintaining sustainable fisheries.

Insights of using microbial material in fluoride removal from wastewater: A review - Linlin Cui; Junjun Wang; Hao Zhou; Shiyu Shao; Jue Kang; Xinyi Yu; Hongbo Zhao; Li Shen (Journal of Environmental Management, 2024)

Characteristics of iron-sulfur metabolism and acid-producing microorganisms in groundwater contaminated by acid mine drainage in closed coal mines - Yanchang Huang; Ping Lu; Feng Zhang; Hao Chen; Wenliang Zhang; Linlin Lin; Hepeng Xu; Haoran Ding; Tianhang Cheng (Groundwater for Sustainable Development, 2024)

Transformation and environmental risk of 90Sr and 137Cs under extreme rainstorm at a proposed nuclear facility site in China - Jun Zhu; Ying Hao; Chao Chen; Ting Wang; Ke Chen; Linlin Zhang; Aiming Zhang; Tian Xie; Qiulan Zhang (Journal of Environmental Radioactivity, 2024)

The latest activity of the slope fault zone (Pearl River Mouth) in northern South China Sea and implications for earthquake hazard assessments - Liangwei Lv; Zhigang Li; Dawei Wang; Weitao Wang; Xiangming Dai; Fanchang Zeng; Linlin Li; Hao Liang; Gege Hui; Weiwang Long; Peizhen Zhang (Marine and Petroleum Geology, 2024)

Ecological restoration for eutrophication mitigation in urban interconnected water bodies: Evaluation, variability and strategy - Linlin Wang; Huaihao Shao; Yuehua Guo; Hongsheng Bi; Xiaoyu Lei; Shuangliang Dai; Xianzhong Mao; Kai Xiao; Xiaomei Liao; Hao Xue (Journal of Environmental Management, 2024)

PCDH11X mutation as a potential biomarker for immune checkpoint therapies in lung adenocarcinoma - Manjiao Liu; Meijia Yang; Bei Zhang; Sijian Xia; Jie Zhao; Linlin Yan; Yong Ren; Hao Guo; Jie Zhao (Journal of Molecular Medicine, 2024)

A robust transformer-based pipeline of 3D cell alignment, denoise and instance segmentation on electron microscopy sequence images - Jiazheng Liu; Yafeng Zheng; Limei Lin; Jingyue Guo; Yanan Lv; Jingbin Yuan; Hao Zhai; Xi Chen; Lijun Shen; LinLin Li; Shunong Bai; Hua Han (Journal of Plant Physiology, 2024)

A randomised double-blind placebo-controlled trial of a probiotic combination for manipulating the gut microbiota and managing metabolic syndrome - Rui Xiao; Ying Chen; Xiaofeng Zhu; Linlin Wang; Peijun Tian; Xing Jin; Ming Liang; Zehua Chen; Ting Zhang; Long Qian; Qun Wang; Jianxin Zhao; et al. (Food Bioscience, 2024)

Measurement of Elastic Bi-modulus of Rock-type Materials: Insight from comparative and parallel tests - Yan Zhang; Hao Zheng; Huiling He; Peng Sha; Linlin Wang; Shengwen Qi; Xiaolin Huang; Jianhong Ye (Bulletin of Engineering Geology and the Environment, 2024)

EB-Net: an efficient balanced network for accuracy and speed of remote sensing detection - Dehua Zhang; Dechen Wang; Changcheng Yu; Xinyuan Hao; Linlin Liang (International Journal of Remote Sensing, 2024)

Bioaerosols in deodorization covers of wastewater treatment plants: Emission characteristics and health risks - Shan Zhao; Yang Liu; Jiang Chang; Jiawei Wang; Hao Peng; Baocong Cui; Jin Bai; Yanjie Wang; Linlin Hua (Chemosphere, 2024)

Preparation of PEI/La2O3/Polypropylene fiber filter for household water purifiers and investigation of its phosphate reduction and bacterial control - Linlin Hao; Gewei Feng; Zengli Zhai; Mingxuan Li (Journal of Water Process Engineering, 2024)

Melatonin alleviates di-butyl phthalate (DBP)-induced ferroptosis of mouse leydig cells via inhibiting Sp2/VDAC2 signals - Si Yang; Meiwei Chen; Jiahui Meng; Chaoju Hao; Linlin Xu; Jinglei Wang; Jiaxiang Chen (Environmental Research, 2024)

Coagulation-centered three-step approach for removing by-product organic pollutants from tetrabromobisphenol A industrial wastewater: Experimental and theoretic investigations - Linlin Hao; Jingshuang Yan; Mingxuan Li; WeiMin Shao; Ming Zeng (Environmental Research, 2024)

Tissue-specific distribution and bioaccumulation of perfluoroalkyl acids, isomers, alternatives, and precursors in citrus trees of contaminated fields: Implication for risk assessment - Zhaoyang Liu; Shun Liu; Feng Xiao; Andrew J. Sweetman; Qianqian Cui; Hao Guo; Jiayi Xu; Ziyao Luo; Mingxia Wang; Linlin Zhong; Jay Gan; Wenfeng Tan (Journal of Hazardous Materials, 2024)

A novel baking additive: Preparation, characterization, and application of chitosan hydrochloride/carboxymethyl starch sodium nano-gel for wheat bread - Xinlai Dou; Yanling Hao; Ying Sun; Pin Yang; Linlin Liu; Yinyuan He; Yanguo Shi; Chunhua Yang; Fenglian Chen (Food Hydrocolloids, 2024)

The pollution of airborne ARGs and microorganisms during wastewater treatment process and their UV mediated removal mechanism - Yanjie Wang; Hao Chen; Liying Yang; Song Zhang; Kai Yang; Linlin Hua (Journal of Water Process Engineering, 2024)

Grey matter structural alterations in anxiety disorders: a voxel-based meta-analysis - Han Liu; Zeqi Hao; Shasha Qiu; Qianqian Wang; Linlin Zhan; Lina Huang; Youbin Shao; Qing Wang; Chang Su; Yikang Cao; Jiawei Sun; Chunjie Wang; et al. (Brain Imaging and Behavior, 2023)

Applying an ensemble of small models in predicting habitat suitability of invasive M. sallei along the southern coast of China - Hao Dong; Jie Liu; Linlin Zhao; Changdong Liu (Marine Pollution Bulletin, 2023)

An Extreme Gale Event in East China under the Arctic Potential Vorticity Anomaly through the Northeast China Cold Vortex - Wei Tao; Linlin Zheng; Ying Hao; Gaoping Liu (Advances in Atmospheric Sciences, 2023)

Green bond financing, environmental regulation, and long-term value orientation: evidence from Chinese-listed companies - Hailin Wang; Linlin Duan; Hao Zeng (Environmental Science and Pollution Research, 2023)

PM2.5-bound metals and blood metals are associated with pulmonary function and Th17/Treg imbalance: A panel study of asthmatic adults - Nannan Liu; Dan Wang; Jiayu Tian; Xin Wang; Hao Shi; Caihong Wang; Yi Jiang; Min Pang; Xiaozhou Fan; Jing Zhao; Liangpo Liu; Hongyan Wu; et al. (Chemosphere, 2023)

Experimental and theoretic mechanism of successive adsorption of oppositely charged Cu(II) and Cr(VI) onto amine-rich cellulose adsorbent - Linlin Hao; Dongmei Jia; Mengzhu Liu (Environmental Science and Pollution Research, 2023)

Frequency specific alterations of the degree centrality in patients with acute basal ganglia ischemic stroke: a resting-state fMRI study - Hao Chen; Linlin Zhan; Qianqian Li; Chaoguo Meng; Xuemei Quan; Xiaoling Chen; Zeqi Hao; Jing Li; Yanyan Gao; Huayun Li; Xize Jia; Mengting Li; et al. (Brain Imaging and Behavior, 2023)
This study intended to investigate the frequency specific brain oscillation activity in patients with acute basal ganglia ischemic stroke (BGIS) by using the degree centrality (DC) method. A total of 34 acute BGIS patients and 44 healthy controls (HCs) underwent resting-state functional magnetic resonance imaging (rs-fMRI) scanning. The DC values in three frequency bands (conventional band: 0.01–0.08 Hz, slow‑4 band: 0.027–0.073 Hz, slow‑5 band: 0.01–0.027 Hz) were calculated. A two-sample t -test was used to explore the between-group differences in the conventional frequency band. A two-way repeated-measures analysis of variance (ANOVA) was used to analyze the DC differences between groups (BGIS patients, HCs) and bands (slow‑4, slow‑5). Moreover, correlations between DC values and clinical indicators were performed. In conventional band, the DC value in the right middle temporal gyrus was decreased in BGIS patients compared with HCs. Significant differences of DC were observed between the two bands mainly in the bilateral cortical brain regions. Compared with the HCs, the BGIS patients showed increased DC in the right superior temporal gyrus and the left precuneus, but decreased mainly in the right inferior temporal gyrus, right inferior occipital gyrus, right precentral, and right supplementary motor area. Furthermore, the decreased DC in the right rolandic operculum in slow-4 band and the right superior temporal gyrus in slow-5 band were found by post hoc two-sample t -test of main effect of group. There was no significant correlation between DC values and clinical scales after Bonferroni correction. Our findings showed that the DC changes in BGIS patients were frequency specific. Functional abnormalities in local brain regions may help us to understand the underlying pathogenesis mechanism of brain functional reorganization of BGIS patients.

A novel ZnFe2O4 intermediate layer for improving the electrocatalytic performance of Ti/Ce-PbO2 anode toward Levofloxacin removal - Linlin Dong; Zhong Zhuang; Guohua Dong; Hao Zhang; Min Zhu; Zhuanfang Zhang; Ming Zhao; Jinlong Li; Wenzhi Zhang (Journal of Environmental Chemical Engineering, 2023)

Multi-valent mRNA vaccines against monkeypox enveloped or mature viron surface antigens demonstrate robust immune response and neutralizing activity - Niubing Zhang; Xiang Cheng; Yilong Zhu; Ouyang Mo; Huiqing Yu; Liqi Zhu; Juan Zhang; Linlin Kuang; Ying Gao; Ruiyuan Cao; Xiaozhen Liang; Haikun Wang; et al. (Science China Life Sciences, 2023)

Expression analysis, clinical significance and potential function of PLXNB2 in acute myeloid leukaemia - Zhibo Guo; Dan Guo; Desheng Kong; Sicheng Bian; Linlin Zhao; Qi Li; Leilei Lin; Jiali Hao; Lili Sun; Yinghua Li (Molecular Biology Reports, 2023)

Construction of a novel ferrihydrite/MoS2 heterogeneous Fenton-like catalyst for efficient degradation of organic pollutants under neutral conditions - Da Chang; Juanjuan Sun; Chang Wang; Linlin Hao; Ming Zeng (Environmental Science and Pollution Research, 2023)

Insights into gas flow behavior in venturi aerator by CFD-PBM model and verification of its efficiency in sludge reduction through O3 aeration - Hongli Li; Qilei Zhang; Ming Zeng; Jingguo Cao; Qingyu Zhao; Linlin Hao (Journal of Water Process Engineering, 2023)

Strong and continuous MXene/sodium alginate composite fibers prepared by immersion rotary jet spinning process with outstanding electromagnetic interference shielding performance - Guoxin Zhao; Chao Sui; Linlin Miao; Junjiao Li; Lei Wen; Gong Cheng; Chenxi Zhao; Weizhe Hao; Yuna Sang; Jiaxuan Li; Zhuochao Zhang; Yushun Zhao; et al. (Chemical Engineering Journal, 2023)

Hair Selenium of Residents in Keshan Disease Endemic and Non-endemic Regions in China - Yuehui Jia; Ruixiang Wang; Guijin Li; Chen Feng; Lei Qi; Yuanyuan Wang; Shengqi Su; Yuanjie Zou; Xu Liu; Yanan Wang; Yiyi Zhang; Linlin Du; et al. (Biological Trace Element Research, 2023)

Analysing the factors affecting medical waste generation in China - Yanhong Hou; Linlin Jia; Wenting Ma; Jian Li Hao (Sustainable Chemistry and Pharmacy, 2023)

Atomic-level chemical reaction promoting external quantum efficiency of organic photomultiplication photodetector exceeding 108% for weak-light detection - Linlin Shi; Yizhi Zhu; Guohui Li; Ting Ji; Wenyan Wang; Ye Zhang; Yukun Wu; Yuying Hao; Kaiying Wang; Jun Yuan; Yingping Zou; Beng S. Ong; et al. (Science Bulletin, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Bioimmobilization and transformation of chromium and cadmium in the fungi-microalgae symbiotic system - Junjun Wang; Qinghua Tian; Linlin Cui; Jinju Cheng; Hao Zhou; Yejuan Zhang; Anan Peng; Li Shen (Journal of Hazardous Materials, 2023)

Selective recovery of lithium from spent LiFePO4 battery via a self-catalytic air oxidation method - Hao Jin; Jialiang Zhang; Cheng Yang; Linlin Ma; Yongqiang Chen; Chengyan Wang (Chemical Engineering Journal, 2023)

Comprehensively investigating performance and potential mechanism of anammox-based nitrogen removal process with different microbial morphologies under mainstream conditions - Shuang Liu; Xinxin Xu; Hongli Li; Ming Zeng; Linlin Hao; Ruihua Zhao; Jingguo Cao; Nan Wu; Zongpeng Zhang (Journal of Environmental Chemical Engineering, 2023)

Development of effective expanded vermiculite flocculant for enhanced primary treatment of swine wastewater: Lab-scale investigations - Linlin Hao; Juanjuan Sun; Ming Zeng; Chang Wang (Applied Clay Science, 2023)

RETRACTED: Study on the effect of SDBS and SDS on deep coal seam water injection - Lianman Xu; Yajing Li; Linlin Du; Fengshuo Yang; Runjie Zhang; Hao Wei; Gang Wang; Zhe Hao (Science of The Total Environment, 2023)

CuO nanosheets incorporated scrap steel slag coupled with persulfate catalysts for high-efficient degradation of sulfonamide from water - Keke Yin; Linlin Hao; Guiju Li (Environmental Research, 2023)

Pseudo-isotopic substituted (Co0.5Ni0.5)S2 anchoring on V4C3T MXene as an efficient anode for full sodium-ions batteries - Yilin Li; J.M. Cao; Linlin Li; Zeyu Yuan; Dongdong Li; Junzhi Li; Yuming Zhang; Hao Xu; Wei Han; Lili Wang (Chemical Engineering Journal, 2023)

Increased Expression of CD95 in CD4+ Effector Memory T Cells Promotes Th17 Response in Patients with Myasthenia Gravis - Xiaoyu Huang; Jie Zhu; Tan Liu; Fengzhan Li; Tingting Yang; Hao Li; Fei Chen; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; Deqin Geng (Journal of Neuroimmune Pharmacology, 2022)

Traditional fermented soybean products: processing, flavor formation, nutritional and biological activities - Libo Liu; Xiaoqian Chen; Linlin Hao; Guofang Zhang; Zhao Jin; Chun Li; Yuzhuo Yang; Jiajia Rao; Bingcan Chen (Critical Reviews in Food Science and Nutrition, 2022)

Correction to: Synthesis and evaluation of iridium(III) complexes on antineoplastic activity against human gastric carcinoma SGC‑7901 cells - Li Tian; Yuanyuan Zhang; Huiwen Zhang; Yi Zhou; Wenlong Li; Yuhan Yuan; Jing Hao; Linlin Yang; Yunjun Liu (JBIC Journal of Biological Inorganic Chemistry, 2021)

Synthesis and evaluation of iridium(III) complexes on antineoplastic activity against human gastric carcinoma SGC-7901 cells - Li Tian; Yuanyuan Zhang; Huiwen Zhang; Yi Zhou; Wenlong Li; Yuhan Yuan; Jing Hao; Linlin Yang; Yunjun Liu (JBIC Journal of Biological Inorganic Chemistry, 2021)

Relationship between heavy metal consolidation and H2S removal by biochar from microwave pyrolysis of municipal sludge: effect and mechanism - Qingyuan Lin; Jun Zhang; Linlin Yin; Hao Liu; Wei Zuo; Yu Tian (Environmental Science and Pollution Research, 2021)

Removal of ammonia nitrogen from water by mesoporous carbon electrode–based membrane capacitance deionization - Guiju Li; Yaning Cao; Zhen Zhang; Linlin Hao (Environmental Science and Pollution Research, 2021)

PbrPOE21 inhibits pear pollen tube growth in vitro by altering apical reactive oxygen species content - Ming Qian; Linlin Xu; Chao Tang; Hao Zhang; Hongru Gao; Peng Cao; Hao Yin; Lei Wu; Juyou Wu; Chao Gu; Shaoling Zhang (Planta, 2020)

DNA Methylation Analysis of the NR3C1 Gene in Patients with Schizophrenia - Linlin Liu; Jian Wu; Lili Qing; Jiajue Li; Hao Yang; Aicen Ji; Ming Yan; Liping Hu; Shengjie Nie (Journal of Molecular Neuroscience, 2020)

Cutibacterium acnes Type II strains are associated with acne in Chinese patients - Shuyang Zhao; Jiayu Ci; Jinhui Xue; Yaofeng Wang; Xuelong Li; Linlin Hao; Liu Tian; Haiyan Guo; Chengqi Xin; Yujie Zhao (Antonie van Leeuwenhoek, 2020)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

Assessment of the effects of lethal and sublethal exposure to dinotefuran on the wheat aphid Rhopalosiphum padi (Linnaeus) - Denghui Deng; Wenbo Duan; Hao Wang; Kun Zhang; Jianglong Guo; Linlin Yuan; Likui Wang; Shaoying Wu (Ecotoxicology, 2019)

Electrosorptive removal of salt ions from water by membrane capacitive deionization (MCDI): characterization, adsorption equilibrium, and kinetics - Guiju Li; Wenbo Cai; Ruihua Zhao; Linlin Hao (Environmental Science and Pollution Research, 2019)

A miR-511-binding site SNP in the 3′UTR of IGF-1 gene is associated with proliferation and apoptosis of PK-15 cells - Wenzhen Wei; Gang Wang; Yunyun Cheng; Rui Yang; Jie Song; Shan Huang; Haoyang Li; Hongwei Geng; Hao Yu; Songcai Liu; Linlin Hao (In Vitro Cellular & Developmental Biology - Animal, 2019)

Plastic Mulch and Plant Density Influencing Soil Water Content and Yield of Rainfed Maize in North‐Eastern China - Shijun Sun; Zhijun Chen; Hao Jiang; Xudong Zhang; Linlin Zhang; Daocai Chi (Irrigation and Drainage, 2019)
Plastic mulch, in combination with high plant density, is a common practice for rainfed maize production in north‐eastern China. However, the influence of these practices on soil water storage, maize yield and maize water productivity in different precipitation years is not well understood. In this paper, a 3‐year split‐plot field experiment was designed to compare non‐mulching and plastic film mulching in maize at 67 500 and 82 500 plants per ha in 2013, 2014 and 2015, and also 97 500 plants per ha in 2014 and 2015. Results revealed an increasing trend of precipitation in the study area from 1962 to 2015 and that the number of dry years and extreme years (including extreme dry and wet years) was increasing. In the moderately wet year 2013 and the moderately dry year 2015, the combination of 82 500 plants per ha and plastic film mulching produced the highest yield and water productivity (8.2 t ha −1 , 1.7 kg m −3 and 8.3 t ha −1 , 2.3 kg m −3 , respectively) for maize, while in the extremely dry year 2014 the highest yield (5.6 t ha −1 ) occurred with 97 500 plants per ha and non‐mulching. This research might be helpful for smallholder farmers needing optimal agricultural strategies to improve maize production in rainfed areas of north‐east China. © 2018 John Wiley & Sons, Ltd.

Linkage disequilibrium and functional analysis of PRE1 insertion together with SNPs in the promoter region of IGFBP7 gene in different pig breeds - Qingyan Wu; Hao Yu; Wenzhen Wei; Yunyun Cheng; Shan Huang; Hongyu Shi; Songcai Liu; Jichao Xia; Hongyao Jia; Linlin Hao (Journal of Applied Genetics, 2018)

Adsorptive removal of organics from aqueous phase by acid-activated coal fly ash: preparation, adsorption, and Fenton regenerative valorization of “spent” adsorbent - Nannan Wang; Linlin Hao; Jiaqing Chen; Qiang Zhao; Han Xu (Environmental Science and Pollution Research, 2018)

Exosomes derived from human amniotic epithelial cells accelerate wound healing and inhibit scar formation - Bin Zhao; Yijie Zhang; Shichao Han; Wei Zhang; Qin Zhou; Hao Guan; Jiaqi Liu; Jihong Shi; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

A novel short anionic antibacterial peptide isolated from the skin of Xenopus laevis with broad antibacterial activity and inhibitory activity against breast cancer cell - Siming Li; Linlin Hao; Wanguo Bao; Ping Zhang; Dan Su; Yunyun Cheng; Linyan Nie; Gang Wang; Feng Hou; Yang Yang (Archives of Microbiology, 2016)

CspE is Overproduced by Temperature Downshift in the Acinetobacter johnsonii DBP-3 - Dan Su; Linlin Hao; Fuwang Chen; Siming Li; Ahmed Mohamed Abdelrahman; Yu Zhang; Hao Yu; Songcai Liu; Mingtang Li (Current Microbiology, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

MRP1 knockdown down-regulates the deposition of collagen and leads to a reduced hypertrophic scar fibrosis - Yan Li; Longlong Yang; Zhao Zheng; Jihong Shi; Xue Wu; Hao Guan; Yanhui Jia; Ke Tao; Hongtao Wang; Shichao Han; Jianxin Gao; Bin Zhao; et al. (Journal of Molecular Histology, 2015)

Pygo2 siRNA Inhibit the Growth and Increase Apoptosis of U251 Cell by Suppressing Histone H3K4 Trimethylation - Mingcong Li; Linlin Chao; Jian Wu; Hao Xu; Shanghan Shen; Sifang Chen; Xin Gao; Ning Yu; Zhanxiang Wang (Journal of Molecular Neuroscience, 2015)

Highly sensitive fluorescence biosensors for sparfloxacin detection at nanogram level based on electron transfer mechanism of cadmium telluride quantum dots - Wanjun Liang; Shaopu Liu; Jing Song; Chenxia Hao; Linlin Wang; Dan Li; Youqiu He (Biotechnology Letters, 2015)

Erratum to: Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Reducing basal salicylic acid enhances Arabidopsis tolerance to lead or cadmium - Siyuan Tao; Lihong Sun; Chunyan Ma; Linlin Li; Guangzhe Li; Lin Hao (Plant and Soil, 2013)

Effects of Aluminum Exposure on Serum Sex Hormones and Androgen Receptor Expression in Male Rats - Hao Sun; Chongwei Hu; Linlin Jia; Yanzhu Zhu; Hansong Zhao; Bing Shao; Nan Wang; Zhigang Zhang; Yanfei Li (Biological Trace Element Research, 2011)